Убойная сила: [повести] - Пучков Лев Николаевич (Спецназ в Чечне, 2002)
Экземпляры: аб (20210127) / Инвентарный номер: 56205 / Цена: 60.00 / Сис.шифр: Р2 / Авт.знак: П90 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6